Potential Drought of Agricultural Land Due to Soil Damage Based on Land Mapping Unit - Siti Maroah; Mujiyo Mujiyo; Ongko Cahyono; Muhammad Rizky Romadhon; Viviana Irmawati; Nanda Mei Istiqomah (The University of Lampung, 2025)
Sediment deposition in the upstream river areas can cause drought and disrupt agricultural activities. This study aims to analyze the potential for drought in the Keduang Sub Watershed based on the Land Map Unit. The Keduang Sub-Watershed area has high potential for the development of agricultural land for food crops, but is not free from the potential for drought. The study was conducted using a soil survey method that was strengthened by soil sampling and laboratory analysis. Parameters for determining soil damage that causes the potential for land drought include soil physical properties, namely specific gravity, structure, soil color, porosity, permeability, slope, and soil type. The results showed that the potential for drought at the research location was still high. This is influenced by the level of soil damage that varies from low, medium to high. Land drought can be an obstacle to agricultural activities, and improper land management can worsen the situation. Conservative actions to overcome this problem include the addition of organic matter, crop rotation, application of soil cover or mulch, and processing agricultural land according to the contour direction. These activities are expected to overcome soil damage so that the potential for drought can be overcome. Keywords: Conservation activities, Land drought, Physic soil properties, Soil damage.